The universal zero markup drug policy and gastric cancer hospitalization expenses: an analysis of trends and influencing factors in Shanghai from 2014 to 2021 - Yichun Gu; Jiajun Hao; Da He; Hui Sun; Xin Cui; Wenqi Tian; Yulin Zhang; Chunlin Jin; Haiyin Wang (BMC Health Services Research)
Abstract Background The increasing hospitalization expenses for Gastric Cancer (GC) impose a notable economic burden on society. Although the Chinese government has implemented the Universal Zero Markup Drug Policy (UZMDP) to control the growth of hospitalization expenditures, costs have continued to rise. Identifying the factors influencing the hospitalization expenses of GC patients is crucial. This study aimed to analyze the trends and factors influencing hospitalization expenses of GC patients in Shanghai from 2014 to 2021. Methods Data were sourced from the Health Network of Shanghai Economic Information Center. We employed interrupted time series analysis (ITSA) to analyze the trends in various medical expenditures before and after the implementation of the UZMDP. The degree of association between various medical expenditures and hospitalization expenditures of GC patients was calculated by using the new grey relational analysis (GRA). Furthermore, multiple linear regression was employed to identify the influencing factors. Results A total of 23,335 participants were included in this study. The ITSA results showed an increasing trend in hospitalization expenses following the implementation of UZMDP. Drug expenses decreased immediately post-UZMDP, but subsequently began to rise over time. Post-UZMDP, the expenses of medical consumables, examination, and healthcare services all showed an upward trend. The new GRA indicated that the influencing factors of hospitalization expenses, in order of importance, were expenses for drugs, consumables, healthcare services, and examination. Multivariable linear regression analysis revealed that GC patients aged 60 or below incurred lower hospitalization expenses (Coefficient = -780.06, P = 0.0398). However, factors associated with increased hospitalization expenses included longer length of stay (Coefficient = 1753.01, P < 0.001), surgeries (Coefficient = 29,047.26, P < 0.001), and hospitalization in the tertiary hospitals (Coefficient = 25,485.19, P < 0.001) or secondary hospitals (Coefficient = 17,755.12, P < 0.001). Conclusions Hospitalization expenses of GC patients in Shanghai have been rising annually from 2014 to 2021. Despite the implementation of the UZMDP, drug expenses remain a major factor in escalating hospitalization expenses. The hospitalization expenses of GC patients are significantly influenced by several factors, including the demographic characteristics of patients, the severity of diseases, and the levels of hospitals. These findings provide a basis for more effective management of the hospitalization expenses for GC patients.